Optical Control of the GTP Affinity of K‐Ras(G12C) by a Photoswitchable Inhibitor. (30th September 2019) - Ge, Zhihua; Yang, Zhuojin; Liang, Jingshi; Dong, Duoling; Zhu, Mingyan
Abstract: Photocontrol of protein activity is an emerging field in biomedicine. For optical control of a mutant small GTPase K‐Ras(G12C), we developed small‐molecule inhibitors with photoswitchable efficacy, where one configuration binds the target protein and exert different pharmacological effects upon light irradiation. The compound design was based on the structure feature of a previously identified allosteric pocket of K‐Ras(G12C) and the chemical structure of covalent inhibitors, and resulted in the synthesis and characterization of two representative azobenzene‐containing compounds. Nucleotide exchange assays demonstrated the different efficacy to control the GTP affinity by photoswitching of one potent compound PS‐C2, which would be a useful tool to probe the conformation of mutational K‐Ras. Our study demonstrated the feasibility of designing photoswitchable modulators from allosteric covalent inhibitor of small GTPases. Abstract : Photoswitchable inhibition : Compounds were designed by azologazation of an allosteric inhibitor of K‐Ras(G12C). They were able to modify the protein on mutation cysteine. The compounds were able to inhibit GTP binding of the K‐Ras with light control, which could be a useful tool for the study of K‐Ras proteins.